2012
DOI: 10.1007/jhep07(2012)026
|View full text |Cite
|
Sign up to set email alerts
|

Space-like (vs. time-like) collinear limits in QCD: is factorization violated?

Abstract: We consider the singular behaviour of QCD scattering amplitudes in kinematical configurations where two or more momenta of the external partons become collinear. At the tree level, this behaviour is known to be controlled by factorization formulae in which the singular collinear factor is universal (process independent). We show that this strict (process-independent) factorization is not valid at one-loop and higher-loop orders in the case of the collinear limit in space-like regions (e.g., collinear radiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 89 publications
(405 reference statements)
7
133
0
Order By: Relevance
“…Furthermore, recent studies have shown that strict collinear factorization is violated if the observable considered is not sufficiently inclusive [32,33]. As a consequence, coherenceviolating (or super-leading) logarithms appear, which further complicate the resummation of certain observables.…”
Section: (δ)mentioning
confidence: 99%
“…Furthermore, recent studies have shown that strict collinear factorization is violated if the observable considered is not sufficiently inclusive [32,33]. As a consequence, coherenceviolating (or super-leading) logarithms appear, which further complicate the resummation of certain observables.…”
Section: (δ)mentioning
confidence: 99%
“…The required momentum mapping is motivated by general factorization properties in QCD [114,118] and the topological identification in Fig. 12.…”
Section: Momentum Mapping and Ir Singularitiesmentioning
confidence: 99%
“…(3.6). We note that for space-like splitting involving more than two hard partons, collinear factorisation is expected to be violated [47]. At two loops, we write…”
Section: Jhep02(2015)077mentioning
confidence: 99%